Oregano extract additive in diets for Betta splendens (Research, Society and Development, 2020)
The objective of this work was to evaluate the oregano extract (EO) (Origanum vulgare) as feed additive for Betta splendens. Used 40 juveniles of B. splendens, with initial mean weight of 0.30 ± 0.02 g, distributed in a completely randomized design with four treatments and ten repetitions, for 45 days. Treatments consisted of the diet oregano extract free (0% EO) and other three rations added with EO (0.25%; 0.50% and 0.75%). The variables analyzed were: initial weight (IW) and final (FW), mean weight gain (WG), protein efficiency rate, head length (HL), profile index (PI), head index (HI), total length (TL), standard length (SL)and height. As a variable for the evaluation of oxidative stress, the activity of the enzyme catalase (CAT) in muscle tissue was verified. The data of each variable were submitted to ANOVA, Tukey test and regression analysis at 5% probability. There was no effect (p>0.05) of the treatments on the evaluated variables: FW, HL, height, PI, HI and specific growth rate. However, there was an increasing linear effect as the addition of EO in the rations was increased over the WG, SL, TL and CAT. It is therefore recommended to use rations with 0.75% of EO for Betta splendens.